A key role for lipoic acid synthesis during Plasmodium liver stage development. (5th April 2013) - Falkard, Brie; Kumar, T. R. Santha; Hecht, Leonie‐Sophie; Matthews, Krista A.; Henrich, Philipp P.; Gulati, Sonia; Lewis, Rebecca E.; Manary, Micah J.; Winzeler, Elizabeth A.; Sinnis, Photini; Prigge, Sean T.; Heussler, Volker; et al.
Summary The successful navigation of malaria parasites through their life cycle, which alternates between vertebrate hosts and mosquito vectors, requires a complex interplay of metabolite synthesis and salvage pathways. Using the rodent parasite Plasmodium berghei, we have explored the synthesis and scavenging pathways for lipoic acid, a short‐chain fatty acid derivative that regulates the activity of α‐ketoacid dehydrogenases including pyruvate dehydrogenase. In Plasmodium, lipoic acid is either synthesized de novo in the apicoplast or is scavenged from the host into the mitochondrion. Our data show that sporozoites lacking the apicoplast lipoic acid protein ligase LipB are markedly attenuated in their infectivity for mice, and in vitro studies document a very late liver stage arrest shortly before the final phase of intra‐hepaticparasite maturation. LipB‐deficient asexual blood stage parasites show unimpaired rates of growth in normal in vitro or in vivo conditions. However, these parasites showed reduced growth in lipid‐restricted conditions induced by treatment with the lipoic acid analogue 8‐bromo‐octanoate or with the lipid‐reducing agent clofibrate. This finding has implications for understanding Plasmodium pathogenesis in malnourished children that bear the brunt of malarial disease. This study also highlights the potential of exploiting lipid metabolism pathways for the design of genetically attenuated sporozoite vaccines.